Sentence Connectors Analysis Of Lover Album By Taylor Swift - Wagini Gini (UMSU, 2021)
This study deals with the use of coordinating conjunctions in lover album by Taylor Swift. This study aimed to find out the most dominant type of coordinating conjunction, to elaborate the realization of types of coordinating conjunction in that album and the reason for using the dominant type of coordinating conjunction in that album. The source of data was the script of Lover Album. Descriptive qualitative research was applied in this data. The data were classified into types of the coordinating conjunction. The data were analyzed based on the types of the coordinating conjunction. The study found that there were five types of coordinating conjunction, they are For, And, But, Or, and So. There were 242 coordinating conjunctions in that album. The percentages of coordinating conjunction were 22 conjunctions(9,09%) for For, 151 conjunctions (62,39%) for And, 52 conjunctions (21,49%) for But, 5 conjunctions (2,07%) for Or, and 12 conjunctions (4,96%) for So. The realization of types of coordinating conjunction occurred because the lyric has the grammatical reasons. The speakers used types of coordinating conjunctions for indicating something that has many references depends on speaker’s means which can explain words or sentences to be understood listener. The dominant type of coordinating conjunction found in Lover Album was 150(61,98%) for And conjunction because more than the other types as the way to connect word to word or sentence to sentence.